Efficacy of food preservatives and volatile compounds in the control of ochratoxin a production by penicillium species - Vankudoth, Koteswara Rao; Rao, K. Narasimha; Sivadevuni, Girisham; Reddy, S. M. (Proceedings of the National Academy of Sciences, India - Section B: Biological Sciences, 2015)
In the present investigation different volatile compounds and food preservatives were tested for their efficiency in the control of growth and ochratoxin A (OTA) production by Penicillium verrucosum and Penicillium nordicum. Volatiles such as phenols and formic acid which have no residual effect were proved to be effective in checking the growth and OTA production by both the species of Penicillium under study. Vapours of phenols and formic acid significantly inhibited OTA produced by P. verrucosum, while aniline and toluene inhibited the OTA production by P. nordicum to a significant level. A positive correlation coefficient was observed between the growth and toxin production by P. verrucosum (0.55) and P. nordicum (0.66) against different volatile compounds tried. Among food preservatives, sodium acetate and sodium metabisulphate were responsible for total inhibition of OTA production by P. verrucosum at 150 lg/ml concentration. P. nordicum proved to be comparatively more resistant to these substances than P. verrucosum. In conclusion of present investigation, phenol, formic acid, amyl alcohol, propionic acid, sodium acetate and sodium metabisulphate were found to be effective in checking the growth and OTA production by both the species of Penicillium under investigation, and can be exploited in protecting the poultry feed from unwanted mould growth and mycotoxin production.